Percutaneous transluminal renal angioplasty attenuates poststenotic kidney mitochondrial damage in pigs with renal artery stenosis and metabolic syndrome. Issue 5 (5th November 2020) - Farahani, Rahele A.; Afarideh, Mohsen; Zhu, Xiang‐Yang; Tang, Hui; Jordan, Kyra L.; Saadiq, Ishran M.; Ferguson, Christopher M.; Lerman, Amir; Textor, Stephen C.; Lerman, Lilach O.; Eirin, Alfonso
Abstract: Percutaneous transluminal renal angioplasty (PTRA) has been used to treat renovascular disease (RVD), a chronic condition characterized by renal ischemia and metabolic abnormalities. Mitochondrial injury has been implicated as a central pathogenic mechanism in RVD, but whether it can be reversed by PTRA remains uncertain. We hypothesized that PTRA attenuates mitochondrial damage, renal injury, and dysfunction in pigs with coexisting renal artery stenosis (RAS) and metabolic syndrome (MetS). Four groups of pigs ( n  = 6 each) were studied after 16 weeks of diet‐induced MetS and RAS (MetS + RAS), MetS + RAS treated 4 weeks earlier with PTRA, and Lean and MetS Sham controls. Single‐kidney renal blood flow (RBF) and glomerular filtration rate (GFR) were assessed in vivo with multidetector computed tomography, and renal tubular mitochondrial structure and function and renal injury ex vivo. PTRA successfully restored renal artery patency, but mean arterial pressure remained unchanged. Stenotic kidney RBF and GFR, which fell in MetS + RAS compared to MetS, rose after PTRA. PTRA attenuated MetS + RAS‐induced mitochondrial structural abnormalities in tubular cells and peritubular capillary endothelial cells, decreased mitochondrial H2 02 production, and increased renal cytochrome‐c oxidase‐IV activity and ATP production. PTRA also improved cortical microvascular and peritubular capillary density and ameliorated tubular injury and tubulointerstitial fibrosis in the poststenotic kidney. Importantly, renal mitochondrial damage correlated with poststenotic injury and dysfunction. Renal revascularization attenuated mitochondrial injury and improved renal hemodynamics and function in swine poststenotic kidneys. This study suggests a novel mechanism by which PTRA might be relatively effective in ameliorating mitochondrial damage and improving renal function in coexisting MetS and RAS. Abstract : This study shows that renal revascularization attenuates mitochondrial injury and improves renal hemodynamics and function in swine poststenotic kidneys. Our observations suggest a novel mechanism by which renal revascularization might be relatively effective in ameliorating mitochondrial damage and improving renal function in coexisting metabolic syndrome and renal artery stenosis.